Lacticaseibacillus absianus sp. nov., isolated from the cecum of a mini-pig. Issue 3 (16th March 2021) - Bai, Lu; Paek, Jayoung; Shin, Yeseul; Park, Ho-Yong; Chang, Young Hyo
Abstract : A rod-shaped, facultative anaerobic, Gram-stain-positive bacteria, isolated from the cecum of a mini-pig, was designated as strain YH-lac23 T . Analysis of 16S rRNA gene sequences revealed that the strain was closely related to Lacticaseibacillus daqingensis JCM 33273 T (97.9 %), Lacticaseibacillus porcinae KCTC 21027 T (96.2 %) and Lacticaseibacillus manihotivorans KCTC 21010 T (95.7 %). Analysis of housekeeping gene sequences ( pheS and recA ) revealed that the strain formed a sub-cluster with L. daqingensis . The average nucleotide identity value for YH-lac23 T and its most closely related strain ( L. daqingensis ) is 80.7 %. The main fatty acids are C18 : 1 ω9 c and C16 : 0 . The cell wall contains the peptidoglycan of meso -diaminopimelic acid. The G+C content of the genomic DNA is 59.8 mol%. In view of the chemotaxonomic, phenotypic and phylogenetic properties, YH-lac23 T (=KCTC 25006=JCM 33998) represents a novel taxon. The name Lacticaseibacillus absianus sp. nov. is proposed.